PRINCIPLES OF CONTENT FORMATION EDUCATIONAL ELECTRONIC RESOURCE - Zaslavskaya, O.Y. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
The article considers modern possibilities of information and communication technologies for the design of electronic educational resources. The conceptual basis of the open educational multimedia system is based on the modular architecture of the electronic educational resource. The content of the electronic training module can be implemented in several versions of the modules: obtaining information, practical exercises, control. The regularities in the teaching process in modern pedagogical theory are considered: general and specific, and the principles for the formation of the content of instruction at different levels are defined, based on the formulated regularities. On the basis of the analysis, the principles of the formation of the electronic educational resource are determined, taking into account the general and didactic patterns of teaching.As principles of the formation of educational material for obtaining information for the electronic educational resource, the article considers: the principle of methodological orientation, the principle of general scientific orientation, the principle of systemic nature, the principle of fundamentalization, the principle of accounting intersubject communications, the principle of minimization. The principles of the formation of the electronic training module of practical studies in the article include: the principle of systematic and dose based consistency, the principle of rational use of study time, the principle of accessibility. The principles of the formation of the module for monitoring the electronic educational resource can be: the principle of the operationalization of goals, the principle of unified identification diagnosis.